Happiness in Motion: Emotions, Well‐Being, and Active School Travel. (August 2014) - Ramanathan, Subha; O'Brien, Catherine; Faulkner, Guy; Stone, Michelle
ABSTRACT BACKGROUND A pan‐Canadian School Travel Planning intervention promoted active school travel (AST). A novel component was exploring emotion, well‐being, and travel mode framed by the concept of "sustainable happiness." Relationships between travel mode and emotions, parent perceptions of their child's travel mode on well‐being, and factors related to parent perceptions were examined. METHODS Questionnaires were administered to families (N = 5423) from 76 elementary schools. Explanatory variables were demographics (age and sex), school travel measures (mode, distance, accompaniment by an adult, safety, and barriers), and emotions (parent and child). Outcomes examined parent perceived benefits of travel mode on dimensions of well‐being (physical, emotional, community, and environmental). Descriptive statistics, chi‐square tests and hierarchical regression were used. RESULTS Parents and children who used AST reported more positive emotions versus passive travelers. Parents of active travelers reported stronger connections to dimensions of well‐being. AST had the strongest association with parents' perceptions of their child's well‐being, and positive emotions (parent and child) were also significantly related to well‐being on the trip to school. CONCLUSIONS As an additional potential benefit of AST, interventions should raise awareness of the positive emotional experiences for children and their parents. Future research should experimentally examine if AST causes these emotional benefits.